MUSLIM POLE OF THE WORLD ECONOMY AND THE GENIE OF GLOBALIZATION - L. L. Fituni; I. O. Abramova (Vestnik MGIMO-Universiteta)
The article explores a process of gradual consolidation of disparate set of Muslim economies into an increasingly influential, though internally contradictory center of geo-economic and geopolitical gravity in contemporary multipolar world. It uses a theory developed by the authors explaining the patterns of formation and succession of models of global economic development. The article builds upon this theory by testing quantitative and qualitative parameters of the process on a specific geo-economic case.The contemporary developments within the economic basis of the Muslim pole and the practical requirements of economic analysis reveals the need for categorical correction and refinement of political economy. Two following terms «Muslim economy» and «Islamic economy» must be differentiated. «Muslim economy» is a civilizational form of national economies in Muslim countries and an integral part of the global economy, including both the economic life and welfare of the global Muslim population and the economic potential, sustainability and the ability for self-development of the economies of Muslim states. «Islamic Economy» is an economy that implements in practice the primacy of Shariah norms over conventional market norms, procedures and mechanisms. Both of them constitute important material conditions for sustaining the Muslim civilizational identityIn recent academic literature political, legal and religious aspects of Muslims upholding their identity have been sufficiently researched. In contrast the process of Muslim’s world achieving a new qualitative status of a global economic power center (not to speak about its competition with other old and new powers for a place within a new global economic order), is practically absent from the Russian and international research.The authors propose a vision of a new quality of Muslim economies in the global balance of power, in emerging model of the global world order, in financial globalization and global governance – the gradual consolidation of the Muslim world. The article argues that this process is still very far from reaching mature forms. Today it is hardly possible to reliably predict specific configurations of the future self-organization of the «Muslim pole» in the polycentric world and the nature of its influence on specific issues of the global world order. However, the point of no return is already passed, and the painful and contradictory process of development of such a center is unlikely to stop.